2018
DOI: 10.1002/pbc.27094
|View full text |Cite
|
Sign up to set email alerts
|

Crizotinib induces apoptosis and gene expression changes in ALK+ anaplastic large cell lymphoma cell lines; brentuximab synergizes and doxorubicin antagonizes

Abstract: Our data suggest that crizotinib induces apoptosis through orderly changes in cell signaling associated with ALK inhibition. Expression effects of crizotinib and associated apoptosis are antagonized by doxorubicin, but apoptosis is synergized by brentuximab vedotin and possibly vinblastine. These findings suggest that concurrent use of crizotinib and doxorubicin may be counterproductive, while the pairing of crizotinib with brentuximab (or vinblastine) may increase efficacy. Alisertib did not induce expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 72 publications
1
5
0
Order By: Relevance
“…These data collectively demonstrate that an upfront combination of targeted and cytotoxic therapies might be beneficial in the treatment of ALK+ ALCL. This is further corroborated by recent results of brentuximab+chemotherapy combinations in newly diagnosed ALK+ ALCL patients [4,51] and promising in vitro data on crizotinib+brentuximab association [52]. Moreover, the meaning of this work extends to a wider scope since the combinatorial approach represents a relevant strategy in all clinical fields for which resistance represents an urgent problem to be solved.…”
Section: Discussionsupporting
confidence: 77%
“…These data collectively demonstrate that an upfront combination of targeted and cytotoxic therapies might be beneficial in the treatment of ALK+ ALCL. This is further corroborated by recent results of brentuximab+chemotherapy combinations in newly diagnosed ALK+ ALCL patients [4,51] and promising in vitro data on crizotinib+brentuximab association [52]. Moreover, the meaning of this work extends to a wider scope since the combinatorial approach represents a relevant strategy in all clinical fields for which resistance represents an urgent problem to be solved.…”
Section: Discussionsupporting
confidence: 77%
“…Indeed, studies have shown that crizotinib synergizes with brentuximab vedotin, which targets CD30-expressing cells, despite NPM-ALK having been shown to drive CD30 expression. 59 ALK inhibitors are now being added to frontline therapy 60 (e.g., in trial NCT01979536) although this combination has led to some unexpected toxicity. 11 NOTCH1 inhibition may therefore serve as a second-line treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Crizotinib is being evaluated in combination with cytotoxic chemotherapy as a part of front‐line therapy in patients with ALK+ALCL (NCT01979536). In vitro studies have shown synergistic activity with crizotinib and brentuximab vedotin and clinical studies are being designed evaluating this combination 130 …”
Section: Principles Of Managing Ptclmentioning
confidence: 99%